Turkey, migration and the EU: Potentials, challenges and opportunities - Seçil Paçacı Elitok; Thomas Straubhaar (Hamburg University Press, 2012)
In the context of Turkey's accession to the EU, the issue of potential migration from Turkey and its impact upon European labor markets became one of the concerns of the EU, considering Turkey's growing population and young labor force. In 2011, half a century after the bi-lateral agreement between Turkey and Germany on labor recruitment in 1961, migration plays a key role in relations of Turkey with the EU and will even increase its significance - not necessarily for the next fifty years but certainly for the next decade. This book touches upon various aspects of the ongoing debate about the effects of Turkey's accession to the EU upon the migration flows and sheds light on various dimensions of current panorama, addresses policy implications as well as future challenges and opportunities.
urn:nbn:de:gbv:18-3-1187; http://econpapers.repec.org/RePEc:zbw:hwwich:61500; http://econpapers.repec.org/RePEc:zbw:hwwich:61472; http://econpapers.repec.org/RePEc:zbw:hwwich:61497; http://econpapers.repec.org/RePEc:zbw:hwwich:61492; http://econpapers.repec.org/RePEc:zbw:hwwich:61484; http://econpapers.repec.org/RePEc:zbw:hwwich:61476; http://econpapers.repec.org/RePEc:zbw:hwwich:61480; http://econpapers.repec.org/RePEc:zbw:hwwich:61470; http://econpapers.repec.org/RePEc:zbw:hwwich:61499; http://econpapers.repec.org/RePEc:zbw:hwwich:61486; http://econpapers.repec.org/RePEc:zbw:hwwich:61474
Keywords: 330; Hamburg Institute of International Economics; HWWI; Turkey; EU; Germany; Migration; Immigration; Workshop; 2011; EU-Erweiterung; Internationale Wanderung; Auswanderung; Türkei; Einwanderung; Arbeitsmarkt; EU-Staaten; Deutschland